DIAGNÓSTICO SITUACIONAL DAS PRÁTICAS INTEGRATIVAS E COMPLEMENTARES NA ATENÇÃO PRIMÁRIA EM SAÚDE DO MARANHÃO. - SOARES, Rafaela Duailibe (2019)
As a way to strengthen the Brazilian Unified Health System (SUS), expand its actions and enhance care, was created Ordinance No. 971 of 2006 by the Ministry of Health, which established the National Policy for Integrative and Complementary Practices in SUS (PNPIC). The Integrative and Complementary Practices (PIC) encompass approaches that aim to stimulate the natural preventive mechanisms of health problems and recovery. From this perspective, this study aims to perform the situational diagnosis of the Integrative and Complementary Practices in Primary Health Care of the State of Maranhão. This is an ecological, descriptive study with primary data from the 217 municipalities of the state, in which the data collection instrument refers to a questionnaire that was applied to all municipal health or professional secretaries designated by them from April to July 2019. Regarding the results, the response rate was 100% (217 municipalities). Of those responsible for completing the questionnaire, 66.4% (144) were Primary Health Care coordinators and 17.0% (37) health secretaries. Of the municipalities from the State, 55 offer some PIC, representing 25.4%. Regarding the Coordination of PIC, only 2.8% of the municipalities hold this position, among which 50% are occupied by nurses. Among the PIC offered in the State, it was noticed that Phytotherapy and massage therapy are the most offered, being present in 49.1% and 29.1% of the municipalities, respectively. Also noting that 38.6% of the municipalities that perform PIC offer more than one practice. Thus, it is important to highlight that the State Department of Health should invest in the construction of a State Health Policy to institute these practices in the State, as well as investing in the dissemination and knowledge of PIC for municipal health managers and health workers from SUS.